Distributing pieces of a pie: education budgets of the German Länder between party politics and fiscal rule - Brumm, Kai; Hörisch, Felix (Politische Vierteljahresschrift, 2025)
German Länder (federal states) have great leeway in designing education policies. This applies to early childhood, school-based, and tertiary education—and the allocation of money to these policy domains. However, when drafting budgets, state cabinets are confronted with trade-offs because public funds are scarce: While fiscal rules limit public borrowing, Länder are barely entitled to increase taxes autonomously. Thus, budgetary trade-offs must be solved on the expenditure side. This article investigates whether party politics and the “debt brake” shape the composition of states’ education budgets. We distinguish between expenditures for early childhood education and care (ECEC), schools, universities, and other purposes. Using this categorisation, we examine the education expenses of all 16 Länder between 1995 and 2020. To capture budgetary trade-offs, the interdependence of expenditure shares (seemingly unrelated regressions) and the budget constraint (compositional dependent variables) are explicitly modelled. Our findings indicate significant partisan effects: Christian Democrats in government give universities right of way, whereas the left-wing Social Democratic Party and the Free Democrats (FDP) prioritise the expansion of public daycare. Stricter subnational fiscal rules make all parties boost relative spending on ECEC, as the expansion of childcare services was often prescribed by federal law. Nonetheless, parties differ in the speed of this expansion.
Online veröffentlicht: 27 November 2024
Gesehen am 10.07.2025